Clinical and radiographic follow-up after the Wilkie procedure at 28 years: A case report - Piper Wenzel, BS; Joan Maley, MD; Antonio Zafred Marcelino, MD, PhD; Henry Hoffman, MD (Radiology Case Reports, 2024)
Rerouting of the parotid ducts posteriorly to drain into the tonsillar fossae (Wilkie procedure) was initially designed to address drooling in patients with cerebral palsy. This procedure was subsequently modified to include bilateral submandibular gland excision and extended to apply to other etiologies of sialorrhea. Our literature review failed to identify report of long-term follow-up beyond 2 decades following this procedure. We describe a 33-year-old female with spastic cerebral palsy who underwent the Wilkie procedure to treat sialorrhea and, 25 years later, developed right-sided facial swelling and dental infections in association with xerostomia. CT imaging showed symmetric atrophy of the parotid glands with fat replacement interspersed with fibrosis. Ultrasound analysis with shear wave elastography offered the additional interpretation of a greater degree of gland stiffness involving the tail of the recently inflamed right parotid gland compared to the left. This case report identifies long-term complications associated with xerostomia following initial success employing the Wilkie procedure to address sialorrhea. The radiographic evaluation supports the contention that rerouting of Stensen's duct may be associated with chronic obstructive changes to the parotid gland. Ultrasound shear wave elastography supplemented CT imaging by identifying asymmetric stiffness of the parotid glands as was consistent with the more recent right parotid inflammation.